2018
DOI: 10.1093/rheumatology/key139
|View full text |Cite
|
Sign up to set email alerts
|

The Scleroderma Patient-Centered Intervention Network Cohort: baseline clinical features and comparison with other large scleroderma cohorts

Abstract: Although there are some differences, the SPIN Cohort is broadly comparable with other large prevalent SSc cohorts, increasing confidence that insights gained from the SPIN Cohort should be generalizable, although it should be noted that all three cohorts include primarily White participants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
49
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 61 publications
(56 citation statements)
references
References 18 publications
3
49
1
Order By: Relevance
“…First, we used convenience samples to develop the questions and evaluate the measurement properties of the COVID-19 Fears Questionnaire. The demographic (including gender, ethnicity, and country) and medical characteristics of SPIN-COVID-19 Cohort participants are similar, though, to our ongoing SPIN Cohort, which is comparable with other large international SSc cohorts [ 13 ]. Second, this study only included patients with SSc, and item development did not include participants with other chronic medical conditions.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…First, we used convenience samples to develop the questions and evaluate the measurement properties of the COVID-19 Fears Questionnaire. The demographic (including gender, ethnicity, and country) and medical characteristics of SPIN-COVID-19 Cohort participants are similar, though, to our ongoing SPIN Cohort, which is comparable with other large international SSc cohorts [ 13 ]. Second, this study only included patients with SSc, and item development did not include participants with other chronic medical conditions.…”
Section: Discussionsupporting
confidence: 65%
“…We solicited a list of fears during the COVID-19 outbreak from people living with the rare, chronic, autoimmune disease systemic sclerosis (SSc; scleroderma). People with SSc are representative of other groups of patients who are vulnerable due to a pre-existing medical condition; they are at risk of severe complications if infected due to lung involvement [ 12 , 13 ], general frailty [ 12 ], and the use of immunosuppressant drugs [ 14 ]. We used suggestions from 121 people with SSc and content analysis to develop a preliminary 15-item version of a fear measure for people with chronic medical conditions [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…An overall prevalence of physician-reported SSc-ILD of 36.2% was recently reported by the Scleroderma Patient-Centered Intervention Network (SPIN) cohort. 7 A diagnosis of dcSSc was associated with a greater prevalence of ILD of 48.5% as compared with 27.7% in lcSSc. 7 Similar frequencies have been reported in older cohorts, ranging between 30 and 71% in dcSSc and 20.8 and 53% in lcSSc, [8][9][10][11][12][13] with the wide differences in prevalence related, at least in part, to differences in detection methods.…”
Section: Epidemiology Of Ssc-ildmentioning
confidence: 85%
“…However, although the SPIN Cohort constitutes a convenience sample of SSc patients receiving treatment at a SPIN recruiting centre, and patients at these centres may differ from those in other settings, a comparison between SPIN Cohort participants and the European Scleroderma Trials and Research and Canadian Scleroderma Research Group cohorts showed broad comparability. 27 This increases confidence that insights gained from the SPIN Cohort should be generalisable.…”
Section: Discussionmentioning
confidence: 96%